Indonesia-Australia Comprehensive Economic Partnership Agreement (IACEPA) in Economic Recovery During the Covid-19 Period - et. al., Dwi F. Moenardy, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article intends to explain the impact of the IA-CEPA agreement in restoring economic conditions during the Covid-19 period, especially in the fields of trade, investment, health and tourism. IA-CEPA, which takes effect from 5 July 2020, is a comprehensive partnership between Indonesia - Australia in the fields of trade in goods, investment, services, and also economic cooperation. This research is qualitative in nature by collecting data through literature study. The analysis knife in this research is international cooperation and bilateral relations. Apart from discussing trade in goods, the IA-CEPA agreement also encourages strategic partnerships in the fields of investment, economy, health, increasing labor capacity, trade in services, transportation, tourism and so on. The results of this study conclude that the IA-CEPA made a real contribution to economic recovery during the Covid-19 period. In the investment and trade sector, Australia provides loans to Indonesia to help the business world. In the health sector, cooperation is focused on the production of masks, medical devices and medical personnel. Meanwhile, in the field of tourism, the two countries are trying to increase the return of tourist visits by still paying attention to health, safety and tourism needs. Thus, the signing of the IA-CEPA illustrates the realization of good bilateral relations in which the two countries contribute to economic recovery during the Covid-19 period..